2016
DOI: 10.1186/s12889-016-2941-0
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of the health and well-being impacts of school gardening: synthesis of quantitative and qualitative evidence

Abstract: BackgroundSchool gardening programmes are increasingly popular, with suggested benefits including healthier eating and increased physical activity. Our objectives were to understand the health and well-being impacts of school gardens and the factors that help or hinder their success.MethodsWe conducted a systematic review of quantitative and qualitative evidence (PROSPERO CRD42014007181). We searched multiple databases and used a range of supplementary approaches. Studies about school gardens were included if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
140
0
46

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(211 citation statements)
references
References 50 publications
7
140
0
46
Order By: Relevance
“…Second, half of the children in the control group in year 1 switched to the treatment group in year 2, which eliminated most of the selection bias observed in year 1 while the significance levels of the estimated impact remained the same. We note that none of the 18 quantitative impact studies reviewed by Ohly et al (2016) did such a repeated experiment. Third, we controlled for several confounding factors by including them as additional covariates in the regression analysis.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 96%
See 4 more Smart Citations
“…Second, half of the children in the control group in year 1 switched to the treatment group in year 2, which eliminated most of the selection bias observed in year 1 while the significance levels of the estimated impact remained the same. We note that none of the 18 quantitative impact studies reviewed by Ohly et al (2016) did such a repeated experiment. Third, we controlled for several confounding factors by including them as additional covariates in the regression analysis.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 96%
“…This is the first such application to our knowledge. Recent reviews of impact studies on school garden interventions in high-income countries concluded that most studies suffered from selection bias, lack of control of confounding factors, high sample attrition and low sample sizes (Ohly et al 2016;Langellotto and Gupta 2012). Our study does not have many of these shortcomings: The rate of sample attrition was very low, we controlled for several confounding factors, and our sample of children and schools was much larger than used in most previous studies.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
See 3 more Smart Citations